The Influence of Innovation and Service Quality on Customer Satisfaction - Indira Mulyasari Paramastuti Ilham; Muliyadi Hamid; Mujahid Mujahid (Newinera Publisher, 2024)
This research aims to determine the suitability of the influence of innovation and service quality on customer satisfaction at Perumda Air Minum Makassar City. Data collection uses primary data obtained from questionnaires using saturated random sampling, its validity and reliability have been tested, and classical assumptions in the form of Normality, Multicollinearity and Heteroscedasticity have also been tested. The data analysis method uses descriptive analysis techniques, coefficient of determination analysis (R2), multiple regression analysis, partial testing (t test) and simutant test (f test). The results of this research show that the Innovation variable has a positive and significant effect on customer satisfaction at Perumda Air Minum Makassar City. The service quality variable does not influence customer satisfaction at Perumda Air Minum Makassar City. And the innovation and service quality variables simultaneously have a positive and significant effect on customer satisfaction at Perumda Air Minum Makassar City.